Application of Antidromic Conduction Monitoring in Ganglion Radiofrequency Thermocoagulation for Locating Trigeminal Branches in Trigeminal Neuralgia. Issue 3 (2nd March 2015) - Li, Xiuhua; Yue, Jianning; Yang, Liqiang; Yang, Huijie; Zheng, Shuyue; He, Liangliang; Ni, Jiaxiang
Abstract: Objective: The aim of this study was to investigate whether antidromic conduction monitoring (ACM) can be utilized to map the trigeminal system under sedation as a potential substitute for subjective paresthesia description (SPD) during percutaneous ganglion radiofrequency thermocoagulation (PGRT). Methods: Eighty‐two patients with 152 pain divisions of trigeminal neuralgia (TN) were treated by computed tomography (CT)‐guided PGRT. After the puncture needle entered the foramen ovale (FO), sensory and motor stimulation were applied to locate the pain division. And the corresponding voltage values were recorded by patients' SPD. In the following, the proper location was certified by ACM. The corresponding earliest waves and voltage values in the identified trigeminal branch were also recorded to outline a comparison between two methods. Results: The correlation of ACM and patients' SPD with voltage at ≤ 0.5 V was statistically significant ( P < 0.05, r = 0.159; Spearman's rank correlation analysis). Although ACM and SPD showed weak correlation, as their interclass correlation coefficient was significant ( F = 1.868, P < 0.01) with coefficient of internal consistency. Moreover, the two methods had consistency. Kruskal–Wallis test showed that ophthalmic (V1), maxillary (V2), and mandibular (V3) divisions had significant differences for test sensitivity ( H = 15.945, P < 0.01). For comparison of sensitivities with ACM, V3 was most sensitive followed by V2 and then V1. Conclusion: ACM could potentially substitute for SPD of the paresthesias intra‐operatively, enabling greater specificity and eliminating the need to interrupt the administration of anesthetic. These improvements would increase patient satisfaction and practitioner efficiency and accuracy.